PENGARUH CITRA MEREK, KETERLIBATAN DAN PENGETAHUAN PRODUK TERHADAP NIAT BELI PRODUK-PRODUK THE BODYSHOP DI BANDAR LAMPUNG - Sarassasti Ayu Nabila; Aida Sari (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The growth of the cosmetics industry in Indonesia is supported by imported and local cosmetic market activities and for the majority of Indonesian consumers, especially women, cosmetics are a routine need that they always buy and make a very profitable market for cosmetic companies. One of the cosmetic companies that caught the attention of the author was The Body Shop. The Body Shop cosmetic products are a company whose products do not damage the environment and Body Shop products have been well known and in demand by the public in Indonesia, especially in Bandar Lampung because they use natural ingredients that do not contain chemicals with good quality. The purpose of this study was to determine the influence of brand image, product involvement and product knowledge on the purchase intention of The Body Shop products. The sample of this study was 100 respondents taken by nonprobability sampling with the criteria of respondents who had used The Body Shop products. Data collection uses questionnaires, subsequently the data are analyzed. The data analysis tools used are multiple linear regression analysis using SPSS software, simultaneous testing (f test), partial testing (t test) and determination analysis (R2). The results Adjusted R Square coefesiencence study showed a contributionBrand Image (X1), Product Engagement (X2), and Product Knowledge (X3) can explain Purchase Intention (Y) by 76.3%, and the results of the F test are known, the variables brand image (X1), Product Engagement (X2) and Product Knowledge (X3) to Purchase Intention (Y) with a significance coefficient of 0.000. The results of the t-test found that Brand Image (X1), Product Engagement (X2), and Product Knowledge (X3) on Purchase Intention (Y) had a positive influence.This means that the Brand Image (X1), Product Engagement (X2), and Product Knowledge (X3) indicators play a role in influencing each Purchase Intent (Y) variable.